Occurrence of Accelerated Epigenetic Aging and Methylation Disruptions in Human Immunodeficiency Virus Infection Before Antiretroviral Therapy. (2nd November 2020) - Yang, Chen Xi; Schon, Emma; Obeidat, Ma'en; Kobor, Michael S; McEwen, Lisa; MacIsaac, Julie; Lin, David; Novak, Richard M; Hudson, Fleur; Klinker, Hartwig; Dharan, Nila; Horvath, Steve; et al.
Abstract: Background: Whether accelerated aging develops over the course of chronic human immunodeficiency virus (HIV) infection or can be observed before significant immunosuppression on is unknown. We studied DNA methylation in blood to estimate cellular aging in persons living with HIV (PLWH) before the initiation of antiretroviral therapy (ART). Methods: A total of 378 ART-naive PLWH who had CD4 T-cell counts >500/µL and were enrolled in the Strategic Timing of Antiretroviral Therapy trial (Pulmonary Substudy) were compared with 34 HIV-negative controls. DNA methylation was performed using the Illumina MethylationEPIC BeadChip. Differentially methylated positions (DMPs) and differentially methylated regions (DMRs) in PLWH compared with controls were identified using a robust linear model. Methylation age was calculated using a previously described epigenetic clock. Results: There were a total of 56 639 DMPs and 6103 DMRs at a false discovery rate of <0.1. The top 5 DMPs corresponded to genes NLRC5, VRK2, B2M, and GPR6 and were highly enriched for cancer-related pathways. PLWH had significantly higher methylation age than HIV-negative controls ( P = .001), with black race, low CD4 and high CD8 T-cell counts, and duration of HIV being risk factors for age acceleration. Conclusions: PLWH before the initiation of ART and with preserved immune status show evidence of advanced methylation aging. Abstract : Before the initiation of antiretroviral therapy, patients infected with human immunodeficiency virus with preserved CD4 T-cell counts demonstrate significant peripheral blood methylation changes and advanced epigenetic aging. Key genes associated with methylation changes map primarily to cancer-related pathways.